2011
DOI: 10.1097/wnr.0b013e32834298b3
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of precise hand movement by transcranial direct current stimulation

Abstract: The effect of transcranial direct current stimulation (tDCS) on the precise nondominant hand movement was investigated by applying anodal stimulation over the right primary motor cortex. We recruited 14 healthy participants for this single-blind, sham-controlled crossover trial. A circle-drawing task was performed before, immediately after, and at 30 min after 20 min of 1 mA anodal or sham tDCS. Anodal tDCS, compared with sham stimulation, significantly improved the circle-drawing task compared with sham stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 1 publication
0
18
1
Order By: Relevance
“…Previous data has shown improvements of manual motor performance in terms of speed (Boggio et al, 2006; Vines et al, 2006, 2008; Hummel et al, 2010), endurance of muscle force (Cogiamanian et al, 2007), or precision (Matsuo et al, 2011) after atDCS over MI contralateral to the active hand. Here, the effect of atDCS on motor behavior differed among age groups in extent and timing and was dependent on the character of the task performed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous data has shown improvements of manual motor performance in terms of speed (Boggio et al, 2006; Vines et al, 2006, 2008; Hummel et al, 2010), endurance of muscle force (Cogiamanian et al, 2007), or precision (Matsuo et al, 2011) after atDCS over MI contralateral to the active hand. Here, the effect of atDCS on motor behavior differed among age groups in extent and timing and was dependent on the character of the task performed.…”
Section: Discussionmentioning
confidence: 96%
“…On the basis of findings in young healthy participants, it has been suggested that modulating cortical excitability with anodal transcranial direct current stimulation (atDCS) is causally linked to behavioral improvement in the cognitive and motor domain (Nitsche et al, 2003c, 2006; Antal et al, 2004a,b; Fregni et al, 2005; for review Reis and Fritsch, 2011; Sohn et al, 2012). Anodal tDCS over the primary motor cortex (MI) led to enhanced motor performance (Boggio et al, 2006; Vines et al, 2006; Cogiamanian et al, 2007; Matsuo et al, 2011) and increased efficiency of motor learning in healthy participants in a variety of behavioral paradigms (Galea and Celnik, 2009; Hunter et al, 2009; Reis et al, 2009; Stagg et al, 2011a,c). …”
Section: Introductionmentioning
confidence: 99%
“…Online tDCS-mediated effects for visuomotor skill learning (non sequential) for both the upper (Antal, Begemeier, Nitsche, & Paulus, 2008;Antal et al, 2004;Foerster et al, 2013;Matsuo et al, 2011;Zhu et al, 2015) and lower (Shah, Nguyen, & Madhavan, 2013;Sriraman, Oishi, & Madhavan, 2014) limb have also been investigated. Earlier work by Antal and colleagues (2004), showed that anodal stimulation of contralateral M1 or area MT/V5 (an extrastriate area that has been implicated in motion processing) applied during learning improved performance in a visuomotor tracking task when applied concurrently with training (Antal et al, 2004).…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%
“…In this context, increases in M1 neuronal firing rates induced by anodal tDCS increases the maximum voluntary force that the subjects can produce (Tanaka et al, 2009; Salimpour and Shadmehr, 2014) when the reference electrode is supra-orbital (cephalic montage) but not when this reference electrode was placed on the shoulder (Cogiamanian et al, 2007; Lampropoulou and Nowicky, 2013). In addition, anodal tDCS of M1 enhances dexterity such as measured by the Purdue Pegboard (PPT) or the Jebsen-Taylor (JTT) tests (Antal et al, 2004; Boggio et al, 2006; Hummel et al, 2010; Williams et al, 2010; Matsuo et al, 2011; Sohn et al, 2012; Kidgell et al, 2013; Bastani and Jaberzadeh, 2014; Convento et al, 2014). The improvement in motor function is even more marked for fine motor skills compared to grosser skills (Hummel et al, 2010).…”
Section: Application Of the Three Principles Of Polarizationmentioning
confidence: 99%